EFFICIENCY OF MANAGING THE ECONOMY OF UKRAINE AND ITS POST-WAR DEVELOPMENT OBJECTIVES (Development Service Industry Management, 2023)
The article analyzes the main macroeconomic indicators characterizing the level of development of the Ukrainian economy from 1991 to 2022. For the period under analysis, four economic crises of the national economy are identified. The consequences of the fourth crisis, provoked by Russia's war against Ukraine, are considered in more detail. The main achievements and advantages of the Ukrainian economy in the pre-war period related to the agricultural and IT sectors have been determined. Attention is focused on problems and their possible consequences regarding the IT sector in the war and post-war periods. An analysis of the country's foreign economic activity for the period from 1996 to 2022 was carried out, where the relationship between the dynamics of changes in the main indicators of this activity and the gross domestic product is monitored, which confirms the level of export and import dependence of the Ukrainian economy. It has been established that there has been a dynamic reorientation of Ukraine's foreign trade to European markets and new logistics routes. The main components of influence on the development of the national economy in the post-war period are determined. The post-war reconstruction plan of Ukraine was considered structurally and substantively, and the main conditions for its implementation were determined. The priorities of the development of the economy of Ukraine in the post-war period are characterized, emphasis is placed on the problems with human potential and its adaptation to new challenges, as well as the search for new ways of realizing the country's economic potential.
Keywords: management; economic crisis; foreign economic activity; national economy; post-war reconstruction plan; human potential